Effects of Soil Characterization on the Seismic Input. Issue 3 (16th March 2019) - Viti, Stefania; Tanganelli, Marco; D'intinosante, Vittorio; Baglione, Massimo
ABSTRACT: This paper is aimed at determining the effects of the soil characterization on the seismic input to use for seismic assessment. Three different soil profiles have been assembled to represent the stratigraphies found through a proper experimental investigation, carefully described, and alternative seismic site response analyses have been performed. The surface spectra obtained from the seismic site response analysis (SRA) are very different from each other, thus evidencing the importance of carefully describing soil stratigraphy. Furthermore, the comparison among the surface records found for different return periods has shown a limited sensitivity of the SRA to the seismic intensity.